Enemy of None But a Common Friend of All? : An International Perspectiveon the Lender-Of-Last-Resort Function - Giannini, Curzio (IMF Working Papers; Working Paper, 1999)
The paper explores whether and how national lender-of-last-resort practices can be adapted internationally. Nationally, the effectiveness of such practices is based on a blend of resource availability, technical discretion as to the conditions attached, ex ante supervision, and powers of enforcement. Some features of the international environment, however, make it difficult to replicate this structure, which may explain why recent large-scale rescue packages have worked less than satisfactorily. Private contingent credit facilities and IMF lending into arrears in the context of internationally approved, temporary moratoria on foreign debt may nonetheless offer some scope for effective, although limited in aims and resources, international liquidity support, but this would require amending the IMF's Articles of Agreement.